E-Learning in Elementary Education: An Analytical Study on Its Effectiveness - Daud, Khalid (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study aims to assess the effectiveness of electronic learning (e-learning) as perceived by Aspiring Elementary Teachers in Tubod, Lanao Del Norte. The research addresses the growing role of e-learning in education and its impact on teaching practices and student outcomes. A descriptive research design was utilized, with data collected through surveys administered to a sample of Elementary Pre-Service Teachers. The analysis focused on the aspiring teachers' perceptions of how e-learning influenced their teaching methods, classroom engagement, and access to resources. The results indicate that e-learning significantly enhances instructional quality, allowing for greater flexibility in lesson delivery and fostering improved engagement with students/pupils. Teachers also reported that e-learning promotes a more personalized learning experience, adapting to various student needs and learning styles. Additionally, the study found e-learning to be cost-effective, reducing reliance on physical resources and travel. These findings suggest that e-learning is a valuable tool in modern education, contributing to more innovative and efficient teaching practices. The implications of this study highlight the importance of continued investment in e-learning technologies to support educators in adapting to evolving educational demands. The study underscores the growing need for technology integration in education to optimize teaching effectiveness and improve learning outcomes.